Síntese de derivados de n-acetilglicosamina e investigação de sua atividade antimicrobiana - Rozângela Magalhães Manfrini (2007)
In this work is described the synthesis of aryl glycosides derived from Nacetylglucosamine, monomeric unit of chitin polymer, essential component of the fungal cell wall, as potential antifungal and antimicrobial agents. Initially, modification at C-6 position of 4-methylphenyl and 4-methoxycarbonylphenyl N-acetylglucosaminides by azido, amino and acetamido groups was performed. Next is described the synthesis of 3,6- and 4,6-diazido derivatives by reacting the b and a anomers of 4,6-O-dimesylate of the 4- methylphenyl N-acetylglucosaminide with sodium azide. When the reaction was performed with the b anomer of the di-O-mesylated derivative, the sole compound isolated was the 3,6-diazido derivative with D-gulo configuration, arising from the opening of the epoxide formed during the reaction. The reaction of the a anomer of the di-O-mesylated derivative resulted in the isolation of three compounds: the 4,6-diazido derivative of the D-galacto series obtained by direct SN2 displacement of the mesylate groups, and the 3,6-diazido derivative of the D-gulo series and 4,6-diazido derivative of the D-gluco configuration, arising from the opening of the epoxide formed during the reaction. None of the compounds showed antifungal activity against filamentous fungi (Aspergillus niger) and yeast (Saccharomyces cerevisae, Cândida albicans and Cândida tropicallis), when evaluated using the agar diffusion method, in the concentration of 1 mg/mL. In the evaluation of the antibacterial activity against Bacillus subtilis, Micrococcus luteus, Staphylococcus aureus, Escherichia coli e Pseudomonas aeruginosa, by the same procedure, 4-methylphenyl 2-acetamido-4,6-O-benzylidene-2-deoxy-a-D-glucopyranoside showed a diffuse inhibition halo of 24.31 ± 1.63 mm against Bacillus subtilis, in the concentration of 1 mg/mL. Chloranfenicol, used as standard in the concentration of 1 mg/mL, showed an inhibition halo of 22.07 ± 1.82 mm.